Comparative Study of Civil Law and Islamic Law on Unlicensed Pawn Cases in North Jakarta - Silvia Ripa Nurkaromah; Maryam Fany; Rifa Naza Amalia; Raafi Al-Afghany (Journal of Family Law and Islamic Court, 2026)
Pawn agreements (rahn) are widely applied by pawnshops and communities in Indonesia, with a clear legal basis in both civil law and Islamic law. However, in practice it is often not in accordance with applicable regulations. This research uses a qualitative approach with descriptive methods and data collection through structured interviews. Data analysis was conducted using content analysis techniques. The case studied relates to cases of pawning without consent in North Jakarta, with settlements that can be pursued through legal channels or family settlements. Therefore, it is very important to carry out pawn agreements in accordance with legal provisions to avoid similar problems in the future.